Step-by-step explanation:
-x+2y=-6
x-2y=6
x=2y+6
substitute in 2x-3y=11 gives us 2(2y+6)-3y=11
4y+12-3y=11
y=-1
-x+2(-1)=-6
-x=-4
x=4
Answer:
B. x < -1
Step-by-step explanation:
Hello!
Let's put them in order from greatest to least:
Given our possible inequalities, we need to find the inequality that contains all of these values.
The inequality that works is x < -1, as <u>all values are less than -1.</u>
Therefore, the answer is B. x < -1.
44.2%= 287
Let the total attempt = x
(287/x) ×100 = 44.2
287/x = 44.2/100
287/x = 0.442
x = 287/0.442
<h3>x= <u>649 </u></h3>
Hope this will help...
Answer:
8.40
Step-by-step explanation:
Answer:
5- ASA
6- SSS
7- SAS
8- SSS
Step-by-step explanation: